Evaluation of some pharmacological and histological profiles of the effect of an alcoholic extract of the dried roots of mondia whitei (periplocaceae) on albino rats, using projected doses based on the folkloric use of the plant - Ansah, Lorraine (2011)
A thesis submitted to the Department of Biological Sciences, the School of Postgraduate Studies in partial fulfilment of the requirements for the degree of Master of Philosophy (Reproductive Biology),